The lost identity of Mother India: Rape, mutilation and a socio-political critique of Indian society - Paunksnis, Šarūnas (Acta Orientalia Vilnensia, 2010)
Vytautas Magnus UniversityThe article discusses a film by Deepa Mehta, a filmmaker who is a part of the so-called Indian Parallel Cinema, and a critic of Indian culture and society. The main argument of the article is that in the landmark film Earth, Mehta portrays a character to personify the idea of Mother India. Mehta’s vision of Mother India is rendered psychoanalytically as being raped by her sons—something that had started during the partition of India and continues till our times. The article introduces and re-thinks categories of Indianness, rape, alienness, which are vital to our understanding of contemporary Indian culture and society. One of the main operating categories of the article is identity—what it means in our modern times, and what it means to lose it—something that happened in 1947 during the partition, and is still continuing. The article also stands in opposition to the traditional understanding of the Mother—in contemporary times, as it is argued, Mother is not cherished by her Sons, instead, she is raped and mutilated, as a consequence of ontological insecurity and desire for identity.